Incidence of unintended pregnancy among female sex workers in low-income and middle-income countries: a systematic review and meta-analysis. Issue 9 (17th September 2018) - Ampt, Frances H; Willenberg, Lisa; Agius, Paul A; Chersich, Matthew; Luchters, Stanley; Lim, Megan S C
Abstract : Objectives: To determine the incidence of unintended pregnancy among female sex workers (FSWs) in low-income and middle-income countries (LMICs). Design: We searched MEDLINE, PsychInfo, Embase and Popline for papers published in English between January 2000 and January 2016, and Web of Science and Proquest for conference abstracts. Meta-analysis was performed on the primary outcomes using random effects models, with subgroup analysis used to explore heterogeneity. Participants: Eligible studies targeted FSWs aged 15–49 years living or working in an LMIC. Outcome measures: Studies were eligible if they provided data on one of two primary outcomes: incidence of unintended pregnancy and incidence of pregnancy where intention is undefined. Secondary outcomes were also extracted when they were reported in included studies: incidence of induced abortion; incidence of birth; and correlates/predictors of pregnancy or unintended pregnancy. Results: Twenty-five eligible studies were identified from 3866 articles. Methodological quality was low overall. Unintended pregnancy incidence showed high heterogeneity (I²>95%), ranging from 7.2 to 59.6 per 100 person-years across 10 studies. Study design and duration were found to account for heterogeneity. On subgroup analysis, the three cohort studies in which no intervention was introduced had a pooled incidence of 27.1 per 100 person-years (95% CI 24.4 to 29.8; I 2 =0%). Incidence of pregnancy (intention undefined) was also highly heterogeneous, ranging from 2.0 to 23.4 per 100 person-years (15 studies). Conclusions: Of the many studies examining FSWs' sexual and reproductive health in LMICs, very few measured pregnancy and fewer assessed pregnancy intention. Incidence varied widely, likely due to differences in study design, duration and baseline population risk, but was high in most studies, representing a considerable concern for this key population. Evidence-based approaches that place greater importance on unintended pregnancy prevention need to be incorporated into existing sexual and reproductive health programmes for FSWs. PROSPERO registration number: CRD42016029185